Goethe und die Rhetorik - Kramer, Olaf (Rhetorik-Forschungen ;, 2010)
Goethe is still considered one of the great critics of rhetoric, who in his writing did not follow the tradition of the schools of rhetoric. Nevertheless he dealt with questions of rhetoric repeatedly, and he thoroughly studied the works of the authorities in the field of rhetoric in antiquity and his own time. This monograph investigates traces of rhetoric in the works of Goethe with a particular emphasis on its importance and reception in the "genius period", but also in the classical dramas (Tasso, Iphigenia, Faust) as well as in his later poetry and his autobiography.